AB 2200 STATE FIRE MARSHAL: CIGARETTE FIRE SAFETY - MIGDEN; GALLEGOS; TORLAKSON (Tufts Archival Research Center, 2007)
Article describing the introduction of a new bill that would require cigarettes sold or manufactured after a certain date to adhere to certain fire safety standards. Makes violation of the bill a crime.